2012
DOI: 10.1308/003588412x13171221591817
|View full text |Cite
|
Sign up to set email alerts
|

Unoperated severe aortic stenosis: decision making in an adult UK-based population

Abstract: INTRODUCTIONSevere symptomatic aortic stenosis is associated with a poor prognosis, with most patients dying 2–3 years after diagnosis. We analysed the proportion of patients with severe aortic stenosis not referred for aortic valve replacement (AVR) in a UK-based population and the clinical factors contributing to this.METHODSRetrospective analysis of patients with echocardiographic evidence of severe aortic stenosis was performed at a university teaching hospital.RESULTSA total of 178 consecutive patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Clinically, severe stenosis can only be treated with either a mechanical or bioprosthetic valve replacement. Without surgery patient prognosis is between 2–3 years [ 25 ]. Synthetic valves characteristically have a 20-year lifespan, bringing increased mortality risks for patients requiring subsequent valve replacements [ 26 , 27 ].…”
Section: Types Of Cardiovascular Calcificationmentioning
confidence: 99%
“…Clinically, severe stenosis can only be treated with either a mechanical or bioprosthetic valve replacement. Without surgery patient prognosis is between 2–3 years [ 25 ]. Synthetic valves characteristically have a 20-year lifespan, bringing increased mortality risks for patients requiring subsequent valve replacements [ 26 , 27 ].…”
Section: Types Of Cardiovascular Calcificationmentioning
confidence: 99%
“…18 More recently, comorbidity has been highlighted as a reason for non-assignment of symptomatic patients to SAVR. 19 In this study, renal impairment was identified as an independent predictor of AVR denial in symptomatic patients, likely because pre-existing chronic kidney disease is strongly associated with worse outcomes following TAVI. 20 In contrast to medical management, AVR in haemodialysis patients has been shown to result in a significantly lower long-term mortality risk.…”
Section: Discussionmentioning
confidence: 73%
“…Lastly, when the primary reason for not proceeding was mild or unrelated symptoms, these patients had relatively low mortality rates during the first year of follow-up. Previous studies have described reasons for not proceeding with TAVR [6][7][8], however, these studies focused on comorbidities and symptoms and did not benefit from systematically-performed objective evaluations of frailty. This study further adds to the existing body of knowledge by connecting the various reasons for not proceeding with TAVR with projected survival.…”
Section: Discussionmentioning
confidence: 99%